Retrograde Training: Effects on Lower Body Strength and Power - Ferley, Derek D.; Osborn, Roy; Vukovich, Matt (International Journal of Sports Medicine, 2022)
Backward walking and running on positive grades (retrograde training) represents a closed kinetic chain exercise used by rehabilitation specialists for patellofemoral-related injuries. To date, no longitudinal studies exist to support it use. This investigation examined the effects of retrograde training on lower body strength and power in recreational athletes aged 18–50 years over 6 weeks. Thirty-seven subjects were divided into two groups. Group 1 performed retrograde training 3 days∙wk−1 using treadmill speeds, grades and bout durations ranging from 1.6–4.9 m∙sec−1, 2.5–27.5% and 10–30 seconds, respectively (RG, n=19). Group 2 was a control group who continued their normal training (CON, n=18). Pre- and posttests assessed a variety of unilateral and bilateral measures including vertical and linear jumps, one repetition maximum leg press strength, and positive and negative power during weighted squat jumping on a horizontal leg press with a force plate. RG improved significantly in all tests (P<0.05). Mean effect size (ES) of the relative improvement in a majority of tests revealed a moderate to very large ES of RG training (ES range: 0.77–2.71). We conclude retrograde training effective for improving lower body strength and power in recreational athletes.
Keywords: backward walking; backward running; closed kinetic chain; eccentric strength